Bacterial community in soil and tree roots of Picea abies shows little response to clearcutting - Martinović, Tijana; Kohout, Petr; López-Mondéjar, Rubén; Algora Gallardo, Camelia; Starke, Robert; Tomšovský, Michal; Baldrian, Petr (FEMS microbiology ecology, 2022)
Clearcutting represents a standard management practice in temperate forests with dramatic consequences for the forest ecosystem. The removal of trees responsible for the bulk of primary production can result in a complex response of the soil microbiome. While studies have shown that tree root-symbiotic ectomycorrhizal fungi disappear from soil and decomposing fine roots of trees become a hotspot for fungal decomposition, the fate of the bacterial component of the soil microbiome following clearcutting is unclear. Here, we investigated the response of bacterial community composition for 2 years following clearcutting of a Picea abies stand in soil, rhizosphere and tree roots, by 16S rRNA amplicon sequencing. While in the first few months after clearcutting there was no significant response of bacterial community composition in the rhizosphere and soil, bacterial communities associated with tree roots underwent more profound changes over time. Acidobacteria were abundant in rhizosphere and soil, while Firmicutes were strongly represented in the roots. In addition, bacterial communities on decomposing roots were significantly different from those on pre-clearcut live roots. Compared with fungi, the response of bacterial communities to clearcutting was much less pronounced, indicating independent development of the two microbial domains.
Keywords: houby; Pinus; Rhizosphere; RNA, Ribosomal, 16S; root decomposition; forest management; Microbiota; rhizosféra; clearcut; půdní mikrobiologie; Picea; jedle; mykorhiza; Abies; Fungi; smrk; mikrobiota; Mycorrhizae; Plant Roots; Bacteria; Soil Microbiology; Soil; půda; kořeny rostlin; borovice; RNA ribozomální 16S; bacteria